2019
DOI: 10.3892/ol.2019.10406
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 overexpression correlates with clinicopathological parameters and poor prognosis of epithelial ovarian cancer

Abstract: The aim of the present study was to investigate the expression of myosin 9 (MYH9) in epithelial ovarian cancer and to explore its correlation with the clinicopathological parameters and prognosis of epithelial ovarian cancer (EOC). A total of 265 cases of paraffin-embedded ovarian cancer tissues and 41 paratumor tissues which had been pathologically confirmed at the Memorial Hospital of Sun Yat-sen University from 2009 to 2017 were included in the present study. MYH9 expression was investigated with immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Moreover, down-regulating the MYH9 expression inhibited angiogenesis, migration, and invasion of esophageal cancer cells. Consistent with our research results, it was reported that expression of MYH9 is closely related to the malignant degree of cancer, and can be regarded as a marker for evaluating lymph node metastasis and poor prognosis in breast cancer [16], epithelial ovarian cancer [17] and acute myeloid leukemia [18]. Combined detection of vasculogenic mimicry, MYH9 and E-cad may play an essential role in predicting the invasion, metastasis, and progression of patients with ESCC [8,9].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, down-regulating the MYH9 expression inhibited angiogenesis, migration, and invasion of esophageal cancer cells. Consistent with our research results, it was reported that expression of MYH9 is closely related to the malignant degree of cancer, and can be regarded as a marker for evaluating lymph node metastasis and poor prognosis in breast cancer [16], epithelial ovarian cancer [17] and acute myeloid leukemia [18]. Combined detection of vasculogenic mimicry, MYH9 and E-cad may play an essential role in predicting the invasion, metastasis, and progression of patients with ESCC [8,9].…”
Section: Discussionsupporting
confidence: 88%
“…Among the proteins associated with FNDC3B, MYH9 had the highest interaction score and was selected for further analysis (data not shown). MYH9 has been reported to function as an oncogene in most types of cancer, and it plays an important role in tumor cell adhesion, migration, and proliferation 18‐20 . The exogenous and endogenous coimmunoprecipitation showed that FNDC3B could physically interact with MYH9 (Figure 4B), which was verified by the immunofluorescence staining that FNDC3B was colocalized with MYH9 in the cytoplasm of both SUNE‐1 and HNE‐1 cells (Figure 4C).…”
Section: Resultsmentioning
confidence: 68%
“…As a skeleton protein, MYH9 plays an important role in cell adhesion, polarity, migration, and proliferation through mediating the actin‐based contractile motion 32 . MYH9 is recognized as an oncogene, as it is closely related to the progress and poor prognosis of most solid tumors 18‐20 . For example, MYH9 overexpression was induced by LIM kinase 1 (LIMK1) and promoted growth and metastasis by activating MAPK/AKT signaling in colorectal cancer 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, robust prognostic markers to monitor the outcome of patient treatment are also lacking. Currently, CA125 and HE4 are suggested as prognostic biomarkers for ovarian cancer, however they lack specificity and sensitivity in monitoring disease progress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%